The impact of body image-related cognitive fusion on eating psychopathology - Trindade, Inês A. (2014)
Recent research has shown that cognitive fusion underlies psychological inflexibility and in consequence various forms of psychopathology. However, the role of cognitive fusion specifically related to body image on eating psychopathology remained to be examined. The current study explores the impact of cognitive fusion concerning body image in the relation between acknowledged related risk factors and eating psychopathology in a sample of 342 female students. The impact of body dissatisfaction and social comparison through physical appearance on eating psychopathology was partially mediated by body image-related cognitive fusion. The results highlight the importance of cognitive defusion in the treatment of eating disorders.